Highly nonlinear rb-based perovskite nanocrystal chalcogenide glass and method of making
Patent Information
- Application Number
- CN202411104571.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-13
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2044-08-13
AI Technical Summary
但是,Rb离子的小半径使RbPbX3钙钛矿的Goldschmidt容差因子(0.795~0.806)已接近理论极限的0.8,远小于CsPbX3的容差因子(0.851~0.87),意味着制备高质量的RbPbX3钙钛矿存在很大的挑战性
1)我们首次在组成为GeS2-Sb2S3的硫系玻璃中合成了容差因子低至0.806的RbPbI3钙钛矿纳米晶体,获得具有高透过率、高非线性吸收系数和高非线性折射率的Rb基钙钛矿纳米晶复合硫系玻璃,经测试,在700~920nm波长范围内,该Rb基钙钛矿纳米晶复合硫系玻璃具有很高的双光子吸收系数和非线性折射率,其红外光透过率为60~80%,维氏硬度最高可达到283kg/mm2,非线性吸收系数β的最大值为51.3cm/GW,非线性折射率n2的最大值为5.19×10−17m2/W,并且该Rb基钙钛矿纳米晶复合硫系玻璃中所含的RbPbI3钙钛矿纳米晶体不会因为高温而相变,更适用于非线性光子器件;
Smart Images

Figure CN118652052B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of nanocrystalline composite chalcogenide glasses, specifically to a highly nonlinear Rb-based perovskite nanocrystalline composite chalcogenide glass and its preparation method. Background Technology
[0002] Metal halide perovskites (or simply perovskites) are halide crystals with the general molecular formula ABX3. Besides their excellent luminescence and photoelectric conversion properties, perovskites also possess superior nonlinear optical properties such as a wide photon absorption cross section, high nonlinear refractive index, and broadband modulation characteristics, making them a promising candidate for applications in nonlinear photonic devices. However, the photothermal instability of perovskites remains the biggest obstacle to their practical application, especially since the high-energy pumping conditions required for nonlinear photonic devices amplify this drawback.
[0003] All-inorganic perovskites exhibit higher photothermal stability compared to organic-inorganic hybrid perovskites. However, cesium lead halide (CsPbX3) perovskites, a representative of traditional all-inorganic perovskites, suffer from high-temperature phase transitions, which is fatal for nonlinear photonic devices where localized high temperatures may occur. To address this, research has shown that replacing the large-radius Cs ions at the A-site of perovskites with smaller-radius Rb ions from the same group can solve the phase transition problem. The resulting rubidium lead halide (RbPbX3) perovskites not only possess higher stability but also exhibit impressive photoelectric conversion efficiency and high absorption coefficients. However, the small radius of the Rb ion causes the Goldschmidt tolerance factor of RbPbX3 perovskites (0.795–0.806) to approach the theoretical limit of 0.8, significantly smaller than the tolerance factor of CsPbX3 (0.851–0.87), indicating a considerable challenge in preparing high-quality RbPbX3 perovskites. It is evident that Rb-based (RbPbX3) perovskites do not suffer from high-temperature phase transitions, making them more suitable for nonlinear photonic devices. However, there are still no reports on the nonlinear optical properties of Rb-based (RbPbX3) perovskites, and their potential nonlinear refraction and absorption characteristics in different wavelength bands remain unknown. Summary of the Invention
[0004] The technical problem to be solved by this invention is to provide a highly nonlinear Rb-based perovskite nanocrystalline composite chalcogenide glass and its preparation method, addressing the shortcomings of existing technologies. Within the wavelength range of 700-920 nm, this nanocrystalline composite chalcogenide glass exhibits high transmittance, high mechanical strength, high nonlinear absorption coefficient, and high nonlinear refractive index. Its infrared light transmittance can reach 60-80%, and its nonlinear absorption coefficient... β The maximum value is 51.3 cm / GW, and the nonlinear refractive index is... n The maximum value of 2 is 5.19 × 10 −17 m2 / W, the minimum optical limiting threshold can be lower than 100μJ / cm. 2 Furthermore, its RbPbI3 perovskite nanocrystals do not undergo phase transitions due to high temperatures, making them more suitable for nonlinear photonic devices.
[0005] The technical solution adopted by the present invention to solve the above-mentioned technical problems is as follows: a highly nonlinear Rb-based perovskite nanocrystalline composite chalcogenide glass, wherein the nanocrystalline composite chalcogenide glass contains RbPbI3 perovskite nanocrystals with a grain size of 10-100 nm, and the precursor glass of the nanocrystalline composite chalcogenide glass has a molar composition of 92(3GeS2-Sb2S3)-8(RbI-PbI2). The nanocrystalline composite chalcogenide glass is obtained by microcrystallizing the precursor glass at a temperature of 300-320℃ for 1-2 hours.
[0006] The matrix glass in this invention, a highly nonlinear Rb-based perovskite nanocrystalline composite chalcogenide glass, has a molar composition of 3GeS2-Sb2S3. This glass composition is located in the central region of the glass-forming zone of the GeS2-Sb2S3 binary system, exhibiting strong glass-forming properties and high halide solubility, enabling the precipitation of metal halide perovskites within the glass. The perovskite nanocrystals contained in this nanocrystalline composite chalcogenide glass are composed of RbPbI3, which has a Goldschmidt tolerance factor of 0.806, slightly higher than the theoretical limit of 0.8. Therefore, it is relatively easier to synthesize compared to RbPbBr3 and RbPbCl3. To ensure that the RbPbI3 perovskite nanocrystals can precipitate directly after the annealing of the chalcogenide glass and remain in the nucleation state, this invention limits the molar ratio of the 3GeS2-Sb2S3 matrix glass to the RbI-PbI2 perovskite to 92:8.
[0007] This invention involves microcrystallizing the precursor glass of the nanocrystalline composite chalcogenide glass at a temperature of 300–320°C for 1–2 hours, thereby growing the crystal nuclei precipitated in the precursor glass into perovskite nanocrystals with a size of 10–100 nm, ultimately obtaining a highly nonlinear Rb-based perovskite nanocrystalline composite chalcogenide glass inlaid with RbPbI3 perovskite nanocrystals.
[0008] Preferably, the microcrystallization treatment temperature is 310℃. After microcrystallization treatment at 310℃, nanoscale RbPbI3 perovskite nanocrystals precipitate in the 3GeS2-Sb2S3 matrix glass of the precursor glass. The nonlinear absorption coefficient of this RbPbI3 perovskite nanocrystal composite chalcogenide glass was tested. βThe maximum value is 51.3 cm / GW, which is 66% higher than the nonlinear absorption coefficient of the 3GeS2-Sb2S3 matrix chalcogenide glass; the nonlinear refractive index of this RbPbI3 perovskite nanocrystal composite chalcogenide glass is... n The maximum value of 2 is 5.19 × 10 -17 m 2 / W, which increases the nonlinear refractive index by 50% compared to 3GeS2-Sb2S3 matrix chalcogenide glasses. Therefore, the Rb-based perovskite nanocrystalline composite chalcogenide glass of this invention exhibits excellent nonlinear refractive and nonlinear absorption characteristics, making it suitable for the fabrication of nonlinear photonic devices.
[0009] Preferably, the maximum nonlinear absorption coefficient of the nanocrystalline composite chalcogenide glass is... β The maximum nonlinear refractive index is 51.3 cm / GW. n 2 is 5.19 × 10 -17 m 2 / W.
[0010] The preparation method of the above-mentioned highly nonlinear Rb-based perovskite nanocrystal composite chalcogenide glass includes the following steps: S1, Raw material preparation and vacuum packaging Based on the molar composition of the precursor glass: 92(3GeS2-Sb2S3)-8(RbI-PbI2), the required mass of each raw material was first calculated. High-purity germanium, antimony, sulfur, rubidium iodide, and lead iodide raw materials were weighed separately using an electronic balance, with the weighing error controlled within ±0.001g. Then, all raw materials were loaded into a dry, clean quartz tube, and the quartz tube was evacuated to 10°C. -5 Below Pa, the raw material is encapsulated in a quartz tube; S2, Raw material melting and mixing The quartz tube containing the raw material was placed in a swing furnace for high-temperature melting at a temperature of 980°C for 12 hours. After melting, the quartz tube was removed from the swing furnace and then quickly immersed in water at room temperature to quench the molten material. After observing the wall separation, it was immediately removed, and a semi-finished precursor glass was obtained inside the quartz tube. S3, Annealing for stress relief The semi-finished precursor glass, together with the quartz tube, is annealed at a temperature of 255–265°C for 10–14 hours. After annealing, the temperature is lowered to room temperature at a rate of 9–10°C / hour. The quartz tube is then removed from the annealing furnace and opened to obtain the finished precursor glass. S4, Microcrystallization treatment The precursor glass product is subjected to microcrystallization treatment at a temperature of 300-320℃ for 1-2 hours to obtain a highly nonlinear Rb-based perovskite nanocrystal composite chalcogenide glass containing RbPbI3 perovskite nanocrystals with a grain size of 10-100nm.
[0011] Preferably, in step S4, the temperature of the microcrystallization treatment is 310°C.
[0012] Compared with the prior art, the present invention has the following advantages: 1) For the first time, we synthesized RbPbI3 perovskite nanocrystals with a tolerance factor as low as 0.806 in chalcogenide glasses with a GeS2-Sb2S3 composition. This yielded Rb-based perovskite nanocrystal composite chalcogenide glasses with high transmittance, high nonlinear absorption coefficient, and high nonlinear refractive index. Testing showed that within the wavelength range of 700–920 nm, this Rb-based perovskite nanocrystal composite chalcogenide glass exhibited a very high two-photon absorption coefficient and nonlinear refractive index, with an infrared transmittance of 60–80% and a Vickers hardness reaching a maximum of 283 kg / mm². 2 Nonlinear absorption coefficient β The maximum value is 51.3 cm / GW, and the nonlinear refractive index is... n The maximum value of 2 is 5.19 × 10 −17 m 2 / W, and the RbPbI3 perovskite nanocrystals contained in the Rb-based perovskite nanocrystal composite chalcogenide glass will not undergo phase transition due to high temperature, making it more suitable for nonlinear photonic devices; 2) This invention encapsulates all-inorganic perovskite RbPbI3 into chalcogenide glass. The resulting Rb-based perovskite nanocrystal composite chalcogenide glass not only fundamentally solves the problem of perovskite's hygroscopicity, but also endows the Rb-based perovskite nanocrystal composite chalcogenide glass with ultra-high nonlinear optical performance due to the high optical nonlinearity of the chalcogenide glass. More importantly, this invention uses vacuum melting to prepare chalcogenide glass, which can protect the precursor glass from the effects of high-temperature oxidation, and is conducive to the synthesis and growth of RbPbI3 perovskite nanocrystals with low tolerance factor, thereby preparing a highly stable and phase-transition-free high nonlinear Rb-based perovskite nanocrystal composite chalcogenide glass. 3) The size and quantity of RbPbI3 perovskite nanocrystals contained in the Rb-based perovskite nanocrystal composite chalcogenide glass of the present invention can be flexibly adjusted according to the temperature and time of microcrystallization treatment, thereby enabling the control of the corresponding performance parameters. 4) The minimum light limiting threshold of the Rb-based perovskite nanocrystal composite chalcogenide glass of this invention is lower than 100 μJ / cm. 2 It has high optical limiting performance and is a high-performance new type of broadband laser protection material, which can be used as an excellent material for the preparation of high-performance optical limiting devices. Attached Figure Description
[0013] Figure 1 A schematic diagram of the experimental setup used in the Z-scan experiment; Figure 2 Nonlinear absorption curves of the glass samples in the blank group, control group, and examples at the same light wavelength (700 nm) were obtained from the Z-scan experiment. Figure 3 Nonlinear refraction results curves of glass samples from the blank group, control group, and examples at the same light wavelength (700nm) in the closed-pore Z-scan experiment; Figure 4 The transmission spectra of glass samples in the visible light band from 0.5 to 12 μm in the blank group, control group, and examples are shown. Figure 5 XRD patterns of glass samples from the blank group, control group, and examples; Figure 6 Transmission electron microscopy (TEM) images of the glass samples used in the examples; Figure 7 The optical limiting spectra of the glass samples at different wavelengths are shown as comparative examples. Figure 8 The light limiting spectra of the glass sample used in the example are shown at different wavelengths.
[0014] The present invention will be further described in detail below with reference to the accompanying drawings and embodiments.
[0015] The embodiment of the highly nonlinear Rb-based perovskite nanocrystalline composite chalcogenide glass contains RbPbI3 perovskite nanocrystals with a grain size of 10-100 nm. The precursor glass of the nanocrystalline composite chalcogenide glass has a molar composition of 92(3GeS2-Sb2S3)-8(RbI-PbI2). The nanocrystalline composite chalcogenide glass is obtained by microcrystallizing the precursor glass at a temperature of 300-320°C for 1-2 hours.
[0016] The method for preparing the highly nonlinear Rb-based perovskite nanocrystal composite chalcogenide glass in this embodiment includes the following steps: S1, Raw material preparation and vacuum packaging Based on the molar composition of the precursor glass: 92(3GeS2-Sb2S3)-8(RbI-PbI2), the required mass of each raw material was first calculated. High-purity germanium (99.999%, 5N), antimony (5N), sulfur (5N), rubidium iodide (4N), and lead iodide (4N) raw materials were weighed separately using an electronic balance, with the weighing error controlled within ±0.001g. Then, all raw materials were placed into a dry, clean quartz tube, and the quartz tube was evacuated to 10°C. -5Below Pa, the raw material is encapsulated in a quartz tube; S2, Raw material melting and mixing The quartz tube containing the raw material was placed in a swing furnace for high-temperature melting at a temperature of 980°C for 12 hours. After melting, the quartz tube was removed from the swing furnace and then quickly immersed in water at room temperature to quench the molten material. After observing the wall separation, it was immediately removed, and a semi-finished precursor glass was obtained inside the quartz tube. S3, Annealing for stress relief The semi-finished precursor glass, along with the quartz tube, is annealed at a temperature of 255–265°C (about 30°C lower than the glass transition temperature) for 10–14 hours to eliminate internal stress in the glass material. After annealing, the temperature is reduced to room temperature at a rate of 9–10°C / hour. The quartz tube is then removed from the annealing furnace, opened, and the finished precursor glass is obtained. S4, Microcrystallization treatment The precursor glass product is subjected to microcrystallization treatment at 310℃ for 1.5h to obtain a highly nonlinear Rb-based perovskite nanocrystal composite chalcogenide glass containing RbPbI3 perovskite nanocrystals with a grain size of 10-100nm.
[0017] For comparison, blank group and comparative example glasses were selected. The difference from the examples is that the blank group glass is 3GeS2-Sb2S3 matrix glass without the addition of RbPbI3 perovskite raw material; the comparative example glass has not undergone microcrystallization treatment, and the perovskite crystals in the glass are in the nucleation state and have not been completely precipitated.
[0018] Table 1 lists the mechanical and optical properties of different glass samples, among which... H v Represents Vickers hardness. E opg The value represents the optical band gap energy. Table 1 shows that the Vickers hardness values of the comparative example are higher than those of the blank group, indicating that the introduction of perovskite can enhance the mechanical properties of the glass. The hardness values of the examples are all higher than those of the comparative example, indicating that the perovskite nanocrystals precipitated after microcrystallization treatment can improve the overall structure of the glass micronetwork and further enhance the overall mechanical strength of the chalcogenide glass.
[0019]
[0020] For all glass samples, open-aperture and closed-aperture Z-scan experiments were used to determine their nonlinear absorption coefficients and nonlinear refractive indices. The four selected wavelengths were 700 nm, 760 nm, 820 nm, 880 nm, and 940 nm. A schematic diagram of the experimental setup used for the Z-scan experiment is shown below. Figure 1As shown. The laser source was a Ti:sapphire laser (Chameleon Ultra II, USA), with an adjustable excitation range of 680–1080 nm, a repetition rate of 80 MHz, a pulse width of 140 fs, and a power stability of ±3%. The laser beam first passed through a highly reflective mirror, then was split into two beams by a semi-transparent mirror (45% reflectivity and 55% transmittance). One beam served as a reference source for the incident power and was detected by power detector 1. The other beam was focused by a biconvex lens and irradiated onto a glass sample placed on a linear platform. The beam passing through the glass sample was received by power detector 2. The power signals received by power detectors 1 and 2 were input to a Coherent EM2000 dual-channel power meter. During the experiment, the position of the glass sample was adjusted using a stepper motor, and the readings of the dual-channel power meter were recorded, thus obtaining a set of Z-scan data corresponding one-to-one between the glass sample position and the transmitted power. All the above tests were conducted at room temperature.
[0021] Figure 2 The graph shows the nonlinear absorption curves of the glass samples from the blank group, control group, and example at the same wavelength (700 nm) using the Z-scan experiment. The numbers ①, ②, and ③ in the graph correspond to the nonlinear absorption curves of the glass samples from the blank group, control group, and example, respectively. Figure 2 It can be seen that the valley depth (normalized transmittance difference Δ) of the glass sample in the example T v Compared to the blank group and the comparative glass samples, the growth rate showed a significant increasing trend. This phenomenon indicates that the precipitation and growth of perovskite nanocrystals can significantly enhance the overall nonlinear absorption characteristics of chalcogenide glasses.
[0022] Figure 3 The figures show the nonlinear refraction results of the closed-pore Z-scan experiment of glass samples from the blank group, control group, and example at the same light wavelength (700 nm). The numbers ①, ②, and ③ in the figure correspond to the nonlinear absorption results of the glass samples from the blank group, control group, and example, respectively. Figure 3 The results show that the peak-to-valley difference (normalized transmittance difference Δ) of the glass samples in the examples T v-p Compared to the blank group and the comparative glass samples, the nonlinear refractive index of the glass samples in the embodiments also showed a significant increasing trend, indicating that the nonlinear refractive index of the glass samples in the embodiments also showed an increasing trend.
[0023] Table 2 lists the nonlinear absorption coefficients of various glass samples and other perovskite materials at different wavelengths. β and nonlinear refractive index n 2. Nonlinear absorption coefficient of glass samples in the blank group at 940 nm wavelength β and nonlinear refractive index n2 are 0.4 cm / GW and 0.21 × 10⁻⁶ respectively. -17 m 2 / W is the minimum value, and the embodiment at a wavelength of 700 nm has the largest nonlinear absorption coefficient. β and nonlinear refractive index n 2, whose values are 51.3 cm / GW and 5.19 × 10, respectively. -17 m 2 / W.
[0024] Table 3 lists the optical limiting thresholds for various glass samples at different wavelengths. OTL The comparative glass sample had an optical limiting threshold of 953.9 μJ / cm at a wavelength of 940 nm. 2 The maximum value is achieved, and the embodiment at a wavelength of 700 nm exhibits the smallest optical limiting threshold. OTL Its value is 98.9 μJ / cm. 2 It is worth noting that the glass samples in the blank group cannot be subjected to [further testing / processing]. OLT The test was conducted because it lacked sufficient photothermal stability.
[0025] In the glass sample of the embodiment, the presence of nanoscale perovskite crystals in the matrix glass generates new valence states between the valence and conduction bands, enhancing its ability to absorb photons with energy below the band gap. This facilitates electron transitions between band gaps, thus increasing the intensity of multiphoton absorption. As shown in Table 2, the photon energy at 700 nm wavelength and the better resonance effect of the defect states in the nanocrystalline glass sample at the focal point enhance nonlinear absorption and nonlinear refraction. Therefore, compared to other wavelengths, under 700 nm laser wavelength radiation, the nonlinear absorption coefficient of the glass sample increases with increasing microcrystallization time. β and nonlinear refractive index n The nonlinearity of the glass increases significantly, exhibiting stronger nonlinear absorption and refraction effects. Furthermore, the nonlinear parameters of the chalcogenide glass with RbPbI3 perovskite nanocrystals are also higher than those of other inorganic perovskite materials such as CsPbI3, as shown in Table 2. Overall, due to the quantum effect of perovskite nanocrystals—that is, the perovskite nanoparticles confined within the glass matrix cause the valence and conduction bands to decompose into a series of discrete energy levels—the nonlinear characteristics increase with increasing crystallinity at the incident wavelength. Through changes and interactions of electronic quantum states in the light field, the intraband transitions of electrons in the glass matrix increase, leading to changes in nonlinear absorption. Based on the change in nonlinear absorption with light intensity, we can measure the optical limiting threshold of the glass sample to assess its optical limiting capability. Ultimately, we obtained the Rb-based perovskite nanocrystal composite chalcogenide glass with the smallest optical limiting threshold.
[0026]
[0027]
[0028] Figure 4 The transmission spectra of glass samples from the blank group, control group, and examples in the visible light band (0.5–12 μm) are shown. For simplicity, [the following text is incomplete and likely refers to a different image or format]. Figure 4 , Figure 5 In the examples, BASE ChG, GSSR-0H, and GSSR-1.5h represent the glass samples of the blank group, comparative example, and embodiment, respectively. Figure 4 It is evident that all glass samples exhibit high infrared light transmittance across a broad region from near-infrared to mid-infrared.
[0029] Figure 5 XRD patterns of glass samples from the blank group, control group, and examples. From Figure 5 As can be seen, after 1.5 hours of microcrystallization treatment, clearly distinguishable crystal diffraction peaks were produced in the spectrum, which, when compared with the PDF standard card (number 43-0860), shows... Figure 5 It is identified as RbPbI3 crystal (represented by PDF 43-0860 RbPbI3). Figure 6 The transmission electron microscope (TEM) image of the glass sample used in this embodiment is shown. Figure 6 The inset is a high-resolution image of RbPbI3 perovskite crystals within the elliptical frame, showing distinct lattice fringes that confirm the presence of RbPbI3 crystals. Figures 5-6 It can be seen that the changes in the internal crystal structure of the glass sample over time can be summarized as follows: (1) For the glass samples in the blank group, simply by... Figure 5 The XRD pattern shows that the glass sample is homogeneous inside and no crystals are present. (2) For the glass samples in the comparative example, according to Figure 5 The XRD pattern shows that there are tiny crystal diffraction peaks. At this time, the crystal is still in the nucleus state and the aggregation degree is small, so the diffraction peaks are not obvious. (3) For the glass sample in the embodiment, the microcrystallization treatment time was 1.5 hours. According to Ostwald's ripening theory, the nanocrystals inside the glass sample further aggregated, and the crystal size further increased. Figure 5 The XRD pattern indicates that the crystal growth is mature and capable of effective diffraction on each crystal plane, specifically manifested by the presence of resolvable crystal diffraction peaks in its XRD pattern, combined with the PDF standard card and Figure 6 Analysis of the mid-transmission electron microscopy image confirmed that the crystals at this time were RbPbI3 perovskite nanocrystals.
[0030] Figure 7The images show the optical limiting spectra of the glass samples at different wavelengths, serving as a comparative example. Figure 8 The optical limiting spectra of the glass sample used in this embodiment are shown at different wavelengths. Figure 7 and Figure 8 It can be seen that the normalized transmittance of the glass sample decreases with increasing laser input intensity, reflecting its optical limiting characteristics. The laser input intensity at which the normalized transmittance drops to 0.5 is defined as the optical limiting threshold. OLT .
Claims
1. A highly nonlinear Rb-based perovskite nanocrystal composite chalcogenide glass, characterized in that, The nanocrystalline composite chalcogenide glass contains RbPbI3 perovskite nanocrystals with a grain size of 10-100 nm. The precursor glass of the nanocrystalline composite chalcogenide glass has a molar composition of 92(3GeS2-Sb2S3)-8(RbI-PbI2). The nanocrystalline composite chalcogenide glass is obtained by microcrystallizing the precursor glass at a temperature of 300-320℃ for 1-2 hours.
2. The highly nonlinear Rb-based perovskite nanocrystal composite chalcogenide glass according to claim 1, characterized in that, The temperature of the microcrystallization treatment is 310℃.
3. The highly nonlinear Rb-based perovskite nanocrystal composite chalcogenide glass according to claim 1, characterized in that, The maximum nonlinear absorption coefficient of the nanocrystalline composite chalcogenide glass β The maximum nonlinear refractive index is 51.3 cm / GW. n 2 is 5.19 × 10 -17 m 2 / W.
4. The method for preparing the highly nonlinear Rb-based perovskite nanocrystal composite chalcogenide glass according to claim 1, characterized in that, Includes the following steps: S1, Raw material preparation and vacuum packaging Based on the molar composition of the precursor glass: 92(3GeS2-Sb2S3)-8(RbI-PbI2), the required mass of each raw material was first calculated. High-purity germanium, antimony, sulfur, rubidium iodide, and lead iodide raw materials were weighed separately using an electronic balance, with the weighing error controlled within ±0.001g. Then, all raw materials were loaded into a dry, clean quartz tube, and the quartz tube was evacuated to 10°C. -5 Below Pa, the raw material is encapsulated in a quartz tube; S2, Raw material melting and mixing The quartz tube containing the raw material was placed in a swing furnace for high-temperature melting at a temperature of 980°C for 12 hours. After melting, the quartz tube was removed from the swing furnace and then quickly immersed in water at room temperature to quench the molten material. After observing the wall separation, it was immediately removed, and a semi-finished precursor glass was obtained inside the quartz tube. S3, Annealing for stress relief The semi-finished precursor glass, together with the quartz tube, is annealed at a temperature of 255–265°C for 10–14 hours. After annealing, the temperature is lowered to room temperature at a rate of 9–10°C / hour. The quartz tube is then removed from the annealing furnace and opened to obtain the finished precursor glass. S4, Microcrystallization treatment The precursor glass product is subjected to microcrystallization treatment at a temperature of 300-320℃ for 1-2 hours to obtain a highly nonlinear Rb-based perovskite nanocrystal composite chalcogenide glass containing RbPbI3 perovskite nanocrystals with a grain size of 10-100nm.
5. The method for preparing the highly nonlinear Rb-based perovskite nanocrystal composite chalcogenide glass according to claim 4, characterized in that, In step S4, the temperature of the microcrystallization treatment is 310°C.
Citation Information
Patent Citations
Method for passivating perovskite and perovskite solar cell
CN110635039A
Perovskite nanocrystal chalcogenide glass with high optical limiting performance and preparation method of perovskite nanocrystal chalcogenide glass
CN117510075A